PELATIHAN KEPERCAYAAN INTERPERSONAL UNTUK MENINGKATKAN KOHESIVITAS TIM - , Alexandriani Imelda ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this study is to investigate the impact of interpersonal trust training on teams cohession improvement in one soccer school (SSB) at Surakarta. With increasing group cohession is expected to increase the effectiveness of the team. Experiment group (23 subjects) trained by series of interpersonal trust training. Before and after the intervention, interpersonal trust and cohession scale is given to experiment group. Control group (23 subjects) is not be trained and only asked to complete interpersonal trust and cohesivity scale. Control group trained by interpersonal trust training after all of the research processess completed. By using anova, the result indicated that team cohession issignificantly improve after interpersonal trust training (p < 0,01).